Application of the Pieces Method in the Analysis and eval_uation of Satisfaction Levels in SMARD Applications - Krisnantia Putra Setyawan; Frederik Samuel Papilaya (Jurnal Indonesia Sosial Teknologi, 2024)
At this time, technological advances are developing rapidly, many have taken advantage of technology to help and facilitate the data processing process for users, one of which is in the office. There is a data processing and data transmission application developed by official organizations, the Population and Civil Registration Office of Semarang Regency has a division or section that develops a data processing application called SMARD. This study aims to obtain what affects the satisfaction of every SMARD application user. The method used to analyze and eval_uate the level of user satisfaction in the SMARD application is PIECES (performance, information, economics, control, efficiency, and service). This study uses a quantitative approach, performance, information, economy, control, efficiency, and service. The average result of SMARD application user satisfaction reached 4.03. It means that users are satisfied with the SMARD application.